Set-Theoretic Approach to Maturity Models - Lester Allan Lasrado (Copenhagen Business School (CBS), 2018)
Despite being widely accepted and applied, maturity models in Information Systems (IS) have been criticized for the lack of theoretical grounding, methodological rigor, empirical validations, and ignorance of multiple and non-linear paths to maturity. This PhD thesis focuses on addressing these criticisms by incorporating recent developments in configuration theory, in particular application of set-theoretic approaches. The aim is to show the potential of employing a set-theoretic approach for maturity model research and empirically demonstrating equifinal paths to maturity. Specifically, this thesis employs Necessary Condition Analysis (NCA) to identify maturity stage boundaries as necessary conditions and Qualitative Comparative Analysis (QCA) to arrive at multiple configurations that can be equally effective in progressing to higher maturity. Furthermore, this thesis prescribes methodological guidelines consisting of detailed procedures to systematically apply set theoretic approaches for maturity model research and provides demonstrations of it application on three datasets. The thesis is a collection of six research papers that are written in a sequential manner. The first paper reviews literature on maturity models in IS, identifies research gaps and proposes use of configurational theory to address these challenges. The second paper conceptualizes stage boundaries as necessary conditions and demonstrates the application of Necessary Condition Analysis (NCA) on a social media maturity dataset. Building on the second paper, the third paper conceptualises maturity stage characteristics in terms of configurations using Qualitative Comparative Analysis (QCA). Overall, the third demonstrates empirically the existence of multiple paths to maturity and provides IS researchers with a six-step procedure and detailed guidelines to systematically apply set theroretic approaches to maturity models (STAMM). The fourth paper then uses the social media maturity dataset, computes maturity scores using different quantitative methods prescribed in maturity models literature and proposes recommendations for maturity model designers. The fifth and sixth papers are demonstrations of applicability of STAMM on different datasets. The fifth replicates and extends a prior research study on ITIL maturity and compares the findings with the results using STAMM. Finally, the sixth paper argues for a multi-method approach by combining STAMM and PLS-SEM in understanding the conditions associated with IT service management (ITSM) maturity. This PhD thesis contributes to the academic discussion on how maturity occurs through configurations. The key contribution is STAMM, a set-theoretic procedure model and method, which employs FsQCA and NCA to empirically demonstrate multiple paths to maturity (or equifinality). It also contributes to set-theoretic approaches, in particular QCA and NCA. Finally, this thesis contributes to multimethod approach by harmoniously integrating PLS-SEM, QCA and NCA, thus adding to the limited body of multi-method literature.
hdl:10398/9621
Keywords: 650